THE FAILURE OF AIR CONDITIONING SYSTEM IN B737NG AIRCRAFT - Anindia Istikomah (Vortex, 2020)
The analysis done by the FMEA and RCFA methods shows that the main cause of the damage because of the accumulation of impurities. And it often occurs in the Heat Exchanger (Hx) component. In Indonesia with the special condition  where the air has a relatively higher humidity and air temperature, it is recommended to clean the heat exchanger more frequently to prevent dirt build up and avoid the problem of AC in producing hot air on the ground. In the standard maintenance manual the heat exchanger must be cleaned with 2000 FC (Flight Cycle) intervals, then the heat exchanger cleaning interval is changed to around 1000 FC (Flight Cycle) based on calculations performed by GMF